2020
DOI: 10.1007/s11205-020-02367-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Conditional Cash Transfer on Multidimensional Deprivation of Young Women: Evidence from South Africa’s HTPN 068

Abstract: Despite the growing popularity of multidimensional poverty measurement and analysis, its use to measure the impact of social protection programs remains scarce. Using primary data collected for the evaluation of HIV Prevention Trials Network (HPTN) 068, a randomized, conditional cash transfer intervention for young girls in South Africa that ran from 2011 to 2015, we construct an individual-level measure of multidimensional poverty, a major departure from standard indices that use the household as the unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 75 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…In a synthesis of national representative Demographic and Health Surveys data from 33 countries in sub-Saharan Africa (covering the period between 2004 and 2015), Melesse et al [34] found that girls with less education (none or primary) initiated sex 2.2 years earlier, were married 4.4 years earlier and had their first child 2.5 years earlier than girls with secondary or higher education. These results re-affirm the need for integrated multidimensional interventions (including conditional and unconditional cash transfers, savings-led economic empowerment schemes, among others) that can help to not only keep girls in school but also help to improve their health outcomes [4,35,36].…”
Section: Discussionmentioning
confidence: 59%
“…In a synthesis of national representative Demographic and Health Surveys data from 33 countries in sub-Saharan Africa (covering the period between 2004 and 2015), Melesse et al [34] found that girls with less education (none or primary) initiated sex 2.2 years earlier, were married 4.4 years earlier and had their first child 2.5 years earlier than girls with secondary or higher education. These results re-affirm the need for integrated multidimensional interventions (including conditional and unconditional cash transfers, savings-led economic empowerment schemes, among others) that can help to not only keep girls in school but also help to improve their health outcomes [4,35,36].…”
Section: Discussionmentioning
confidence: 59%
“…We categorised interventions assessed for acceptability both by type of intervention, based on their key components (see Figure 3), and stated objectives of the interventions (see Figure 4). In terms of type of intervention, interventions were classified as HIV or HPV vaccine interventions (10), E-health (10), HIV testing interventions (8), support group interventions (7), contraceptive interventions (6), voluntary medical male circumcision programs (VMMC) (4), school-based sexual and reproductive health education (4), economic support programs (4) and pre-exposure prophylaxis (PrEP) (2). Five studies did not fit into the above intervention categories and were grouped as ‘other’; they consisted respectively of nutritional therapy, a psychosocial - home based care intervention, a counselling support intervention to address substance abuse, cervical cancer screening and a rectal microbicide intervention for HIV prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in Southern Africa, of which 32 jointly in South Africa and Uganda. The majority of interventions assessed for acceptability could be classified as HIV or HPV vaccine interventions (10), E-health (10), HIV testing interventions (8), support group interventions (7) and contraceptive interventions (6). The objectives of most interventions were linked to SDG3, specifically to HIV and sexual and reproductive health.…”
mentioning
confidence: 99%
“…There exists ample literature highlighting the important role of CCT programs in eradiating financial constraints that affect school enrollment and dropout decisions (Adato et al 2016;Biggeri et al, 2018;Davis et al, 2016;Kilburn et al, 2020). Bangladesh started a cash transfer program in 1993 under the guidelines of the International Development Association (IDA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results suggested an increase in girls' participation by 8.2 % in schools in response to CCT programs. Moreover, Kilburn et al (2020) conducted an empirical study on Malawi and found out a strong positive impact of cash transfers on increased enrollment rate and decreased dropout rate. Highlighting the importance of these cash transfer programs, Kilburn et al (2017) and Purba (2018) suggested a continuity of such programs with greater efficiency as these programs help to increase student enrollment.…”
Section: Literature Reviewmentioning
confidence: 99%